Marine biology function, biodiversity, ecology - Levinton, Jeffrey S. 1946- (Oxford University Press, 2022)
"With its clear and conversational writing style, comprehensive coverage, and sophisticated presentation, "Marine Biology: Function, Biodiversity, Ecology", Sixth Edition, is regarded by many as the most authoritative marine biology text. Over the course of six editions, Jeffrey Levinton has balanced his organismal and ecological focus by including the latest developments on molecular biology, global climate change, and ocean processes"--
Keywords: Marine biology; Marine biology / Textbooks; Textbooks